New Conflicts, New Orientalists: How Military Theorists Reproduced Orientalism in Twenty-First Century - Hasan Deniz Pekşen (Alternatif Politika)
Efforts to understand the twenty-first century conflicts have led to the appearance of many unconventional studies. While many analyze the new conflicts as the method of the “weak”, others analyzed twenty-first century conflicts as the method of specific “cultures.” In this study, it is argued that many military theorists, who use the cultural analysis of new conflicts, also reproduce new forms of orientalism. Based on this argument, the study questions whether the orientalist discourse used in these works maintains continuity with the classical orientalist discourse or creates a new one specific to the twenty-first century. To answer that, first, drawing on Edward Said's and Patrick Porter’s works, classical orientalism is outlined. Then, to make the comparison, neo-orientalist theses regarding the continuity of colonialist and Euro-Centric perspectives are examined. Finally, selected texts and expressions from Counterinsurgency and Fourth Generation Warfare literatures are analyzed. As a result, it is concluded that these studies reproduce Orientalism and there is a continuity.